Modern versus traditional: visual aids in the teaching of English vocabulary among Form 1 ESL students - Phang, Biao Li (2019)
The importance of vocabulary for a language user to be competent in using the target language has been circulating for many years. Functioning as a pre-requisite to four main language skills in a language, English as Second Language students in Malaysia are yet to show satisfying command over English vocabulary to perform language tasks. Using a descriptive approach along with purposeful selection of Form 1 ESL students from SMK Sentosa, Kampar, Perak for ten weeks, this study aimed at determining if the ESL students were weak in English vocabulary; if visual aids, particularly the interactive white board was able to help the ESL students, and obtaining the perceptions and preferences among ESL students and teachers on using traditional and modern visual aids to teach English vocabulary. Employing pre and post-tests, intervention and interviews, findings showed that not only all the ESL students involved improved significantly, visual aids regardless of traditional or modern were also positively viewed by both ESL students and should be employed in all subjects rather than English language itself. Future researchers were recommended to explore not only nouns as did in this study, but also other parts of speech and in a longer duration.